Estudo do processo de soldagem MIG/MAG para aplicações de revestimentos em aços usando a liga AWS ERNiCrMo-3 na posição horizontal - Marques, Felipe Wendrio da Silva (2022)
The use of welding coatings has broad applicability in the industry as it provides the substrate with characteristics such as resistance to corrosion and wear. Some steels, such as HSLA (high strength and low alloy) and C-Mn steels, are coated with special alloys, such as nickel alloys, which have excellent corrosion resistance. The demand for increasing the viability of the application and economic attractiveness of the welding overlay technique makes it essential to carry out an in-depth study of welding operational variables to produce coatings without defects, with a low dilution level, which meets the needs imposed by the industry. Thus, this study aims to produce coatings of the AWS ERNiCrMo-3 by the MIG/MAG welding process in the horizontal position through a systematic study, making it possible to evaluate the effect of a series of operational variables on the characteristics of the weld beads. The effects of certain levels of control factors (reference voltage (Ur), wire feed speed (Valim), inverse of the rise inductance (Ks) and inverse of the fall inductance (Kd)) in the qualitative aspects of the passes and some indicators measured through data acquisition. From selecting the best parameters, it was possible to choose the parameters of the controlled short-circuit mode, resulting in passes with better stability and little splash. Furthermore, the torch oscillation parameters were evaluated for the types of triangular weaving, switchback and the linear trajectory of the torch in some geometric variables, especially in the dilution. The Higuchi test was applied to evaluate the deposition of the second layer using a quenched base metal. Single weld beads were also deposited on as-received base metals, aiming to assess the heat-affected zone (HAZ) microhardness and microstructure profiles for applying the double-layer controlled deposition technique (DL-CDT). The parameter with the highest energy to be deposited in the second layer was deposited in pulsed mode, with twice the heat input of the first layer. Through the analyzes it was verified that no condition was approved through the Decision Diagrams. In addition, passes through the quenched base metal produced more extensive and refined heat-affected zones. The coatings made had the HAZ consisting predominantly of bainite, with the presence, in general, of decarburization near the interface with the fusion zone. It was not possible to obtain significant microhardness reductions in the coatings due to the non-fulfillment of all the necessary criteria to guarantee the effectiveness of DL-CDT. In addition, some coatings showed points of discontinuity between the HAZ and the molten zone, showing the need to use a higher arc power provided by welding parameters and a more suitable shielding gas, although at a higher cost.